Análise, integração e visualização de dados urbanos de múltiplas fontes heterogêneas - Pedro Magalhaes Fortini (2018)
The rapid progress of urbanization and the consequent increase in the urban population create great challenges for those responsible for urban planning. These challenges include various areas, such as the environment, energy consumption, transport, and others. Although there are many problems and challenges, the massive amount of information generated every day in urban environments allows envisioning solutions for them. However, as such sources of information are heterogeneous and involve a large amount of data, there are major challenges for their use. The objective of this dissertation is to study techniques and methods that allow the analysis, integration and visualization of urban data from multiple heterogeneous sources, aiming to create a generic model for urban data analysis, focusing mainly on transport and traffic data. In order to demonstrate the feasibility, applicability and validity of the model, two case studies were created: the Urban Transit Fingerprint and the Urban Map of Access to Basic Services. The main idea of the Urban Transit Fingerprint visualization is to compare the accessibility and urban mobility in any part of a city using public transportation (specifically buses) and private transportation. The Urban Map of Access to Basic Services was created with the objective of: determining the efficiency of the routes produced by the public and private transportation systems of a city, comparing accessibility to basic services using such transportation systems, and contrasting such information with data on quality of life. Results show wide discrepancies in the effort a public transit user has to make for her mobility in various regions of each city, as compared with individual modes of travel. These results help explaining the reasons behind the sharp drop in the number of transit users in Brazilian cities over the last years, thus calling on urban planners to devise public policies in the search for better solutions.